Gonadal tumor risk in pediatric and adolescent phenotypic females with disorders of sex development and Y chromosomal constitution with different genetic etiologies - Lu, Liangsheng; Luo, Feihong; Wang, Xiang (Frontiers in Pediatrics, 2022)
Objectives: This retrospective study sought to investigate the risk and proportion of gonadal neoplasms in phenotypic female pediatric patients with DSD and the presence of the Y chromosome and different genetic backgrounds in a single Chinese center. Methods: From January 2012 to December 2020, pediatric and adolescent patients with DSD and the presence of the Y chromosome who had unambiguous female genitalia and underwent bilateral gonadectomy or gonadal biopsy were included in this study. Data of the patients were collected including demographics, karyotype, laboratory test results, gross pathology, and histology of gonadal tissue were collected. The patients were divided into three groups based on their different genetic backgrounds, and the percentage of gonadal tumors was calculated to assess the risk of gonadal tumor and malignancy by etiology. Results: Twenty-two patients with DSD and unambiguous female phenotype with Y chromosome were recruited. Mean age was 10.91 ± 4.99 years (9 months to 19 years). Gonadal neoplasianeoplasms were was confirmed in six (27.3%) cases by pathological examination of surgical gonadal tissue samples from surgery. Among 44 gonadal samples from these 22 patients, the following were identified: five gonadoblastomas, three dysgerminomas, and two Leydig cell tumors. The youngest patient with a tumor was a 2-year-old girl with 46,XY complete gonadal dysgenesis (46,XY CGD or Swyer Syndrome) Swyer’s syndrome and bilateral gonadoblastoma. Patients with 46,XY complete gonadal dysgenesis (4/6; 66.7%) had the highest tumor occurrence rate. Among 10 patients with Turner syndrome with the presence of the Y chromosome, only one patient was diagnosed with gonadal tumor. Only one among six patients with 46,XY androgen synthesis/action disorders was diagnosed with Leydig cell tumor. Conclusions: Pediatric patients with 46,XY complete gonadal dysgenesis had significantly increased risk of developing gonadal tumors and underwent prophylactic gonadectomy as soon as the diagnosis was confirmed; whereas those with Turner syndrome with Y chromosome and 46,XY androgen synthesis/action disorders had a relatively low risk. In view of the limited number of patients, a large multicenter study with close follow-ups are needed to support these conclusions.